Transformasi Digital dalam Pendidikan: Menuju Masa Depan Belajar Yang Lebih Baik - Juhra, Al (Pencerah, 2025)
This study aims to analyze the role of digital transformation in improving the quality of education by integrating digital technology into the learning process. Specifically, it examines its impact on learning effectiveness, the expansion of educational access, and the development of 21st-century skills students require. The research employs a descriptive-analytical approach, drawing on a literature review of scholarly articles, policy reports, and previous studies on the implementation of digital technology in educational institutions. The findings indicate that digital transformation significantly enhances learning quality through personalized instruction, increased interactivity, and flexible access to education, free from the limitations of space and time. Furthermore, the use of digital technology promotes digital literacy and strengthens students’ readiness to face future challenges. However, the study also identifies several challenges, including the digital divide, limited infrastructure, and the readiness of human resources and educational institutions. In conclusion, digital transformation holds substantial potential to revolutionize the education system if supported by adaptive policies, improved teacher competencies, and equitable access to technology to ensure effective and sustainable implementation.